Rat AA-26: behavioral pharmacology science pioneer. - Brady, J V (1991)
Rat AA-26, despite 1950s "state of the art," nonetheless generated the first set of behavioral pharmacology cumulative records to appear in the weekly journal Science, the century-old publication of the American Association for the Advancement of Science. The laboratory exploits of this dedicated animal called early attention to the methodological fruits of a marriage between pharmacology and the experimental analysis of behavior.